Development of Animated Picture Media to Improve Early Reading Skills in First-Grade Elementary School Students - Ridhani; Zelhendri Zen; Darmansyah; Zuwirna; Rayendra (Postgraduate, University of Mataram, 2026)
Early reading skills serve as the primary foundation for literacy mastery among elementary school students. However, many first-grade students still face difficulties in recognizing letters, forming syllables, and reading simple words. Therefore, it is necessary to develop engaging and interactive learning media. This study aims to develop animated picture media to improve early reading skills in Indonesian language learning for first-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were first-grade students at SD Negeri 05 Batu Taba, with validation conducted by material experts, media experts, and language experts. Data were collected through validation questionnaires, practicality observations, and reading ability tests (pretest and posttest). The results showed that the developed animated picture media achieved a validity level of 91% (very valid), practicality of 94.6% (very practical), and high effectiveness with an N-Gain score of 0.70. These findings indicate that the animated picture media are effective in improving early reading skills while also enhancing students’ learning motivation through enjoyable and interactive learning experiences.